An Analysis of Enhancing Students’ Grammar Proficiency in The Simple Present Tense Through The Translation Technique at Grade X of SMKS Reformasi Plus Noelbaki: Penelitian - Selfiyani Regina Tungga; Rozita Yusniaty Lodo; Chamelya V.C. Sene (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study analyses the effectiveness of applying the translation technique to enhance students’ grammar proficiency in the simple present tense at grade X of SMKS Reforrmasi Plus Noelbaki. The study was conducted to concentrate on students’ persistent difficulties in comprehending and applying simple present tense structures accurately in both written and speaking context. The translation technique was applied by engaging students in translating sentences from Bahasa Indonesia to English and vice versa, enabling them to recognize grammatical patterns, strengthen structural awareness, and internalize rules of the simple present tense more effectively. The findings reveal the important improvement in students’ mastery of the simple present tense after the applying of translation technique, can serve as a meaningful and supportive technique for teaching grammar.